Morphological and conceptual influences on the real-time comprehension of optional plural marked sentences in Yucatec Maya - Butler, Lindsay K. (Frontiers in Psychology, 2023)
Introduction Psycholinguistic research often focuses on Indo-European and other commonly studied major languages, while typologically diverse languages remain understudied. In this paper, we examine the morphological and conceptual influences on the real-time comprehension of optional plural-marked sentences in Yucatec Maya, an indigenous language of Mexico with a less commonly studied optional plural marking system. Methods Fifty-one speakers of Yucatec Maya participated in a picture-sentence matching experiment carried out in the Yucatan Peninsula of Mexico. Pictures of one, two, or seven humans or animals depicting an intransitive action (conceptual number) were paired with auditorily presented sentences that had no plural marking, one plural, or two plurals (morphological number). Participants indicated by key press whether the picture and the sentence were an acceptable match, and decision time was recorded. Results In the analysis of decision (yes versus no) and accuracy, morphological and conceptual factors interacted. In the analysis of decision time, however, morphological plural marking, but not conceptual number, led to faster decisions. Discussion In light of previous work on the role of conceptual factors in the computation of number agreement, the interaction between conceptual and morphological factors suggests that a language with optional plural marking (or low “morphological richness”) is associated with high conceptual influence on sentence comprehension. Importantly, the results of this study expand the empirical base of language types that have been investigated using psycholinguistic methods.